THE VALUE OF THE SYSTEMIC IMMUNE INFLAMMATION INDEX (SII) IN MIGRAINE PATIENTS TREATED WITH GREATER OCCIPITAL BLOCK TREATMENT - Sadri, Sevil; Ülfer, Gözde; Polat, Burcu (Sanamed, 2023)
Introduction: Neuroinflammation plays a key role in various neurological conditions, including migraine. GON block has been used for both acute and preventive treatment in migraine sufferers. Exploring whether this localized nerve blocking therapy for migraines affects signs of systemic inflammation would be beneficial.Materials and Methods: In this study, a total of 50 migraineurs (comprising high-frequency episodic and chronic migraine) and 60 healthy control volunteers of comparable ages and sexes were enrolled. The neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and SII levels in migraine patients, migraine sufferers, and healthy individuals are compared. This study examined hematological parameters and SII levels used as inflammatory markers in those diagnosed with migraine.Results: It was determined that the mean platelet and PLR values of the case group's subjects were substantially lower than those of the patient group's subjects (p < 0.05). Biochemical characteristics of the cases were examined before and after treatment with greater occipital nerve (GON) block, revealing a statistically significant reduction in attack frequency, severity, and duration (p < 0.001). No significant differences were discovered when compared to post-treatment values (p > 0.05), even though the ratios were greater prior to GON block therapy in other measures.Conclusion: These findings, in our opinion, are linked to the presence of a continuous inflammatory process even in the absence of episodes, supporting systemic inflammation in migraineurs. Thus, SII, an affordable and easily measurable marker in peripheral blood, may serve as a helpful predictive marker for migraine patients scheduled for GON block treatment. Further extensive research is needed to determine whether SII can be an independent prognostic factor in migraine patients.
Keywords: migraine; neuroinflammation; systemic immune inflammation index